O ensino médio politécnico e a avaliação a partir da área de matemática: um estudo de um caso em uma escola estadual no município de Caxias do Sul - Pereira, Simone Beatriz Rech (My University, 2019)
The present dissertation aimed to investigate the conception and evaluation process in the area of Mathematics present in official documents and in evaluation practices, related to the Ensino Médio Politécnico in the state of Rio Grande do Sul, exclusively in a state school in the municipality of Caxais do Sul, on the scope of the 4th Regional Coordination of Education, from 2012 to 2016. The theoretical contribution in which the present study is based is anchored in Freire (1986, 1996, 2001), Afonso (2000), Garcia (2000), Vasconcellos (1998), Esteban (2000), Hoffmann (1993), Luckesi (2018), Saul (1994, 2000, 2015) among others. It is a qualitative and the method used is the Case Study. The formation of the search corpus began with the reading and compilation of institutional documents such as the School Regiment and the Political Pedagogical Project. Interviews with Mathematics teachers and some members of school management who participated in the implementation of the Ensino Médio Politécnico in that school, added up to the composition data construction. For analysis and treatment of the data, Discursive Textual Analysis Moraes; Galiazzi, (2011) was used, enabling the formation of four categories that contemplate the significant advances of a perspective of emancipatory evaluation, the development of the subjects committed to the transformation of the school, the resistance and the alternative formative paths to a qualified and continuius teacher training. The results point to the importance of the reflection about the perceptions and the qualification of the ones involved in learning processes, for the educational actions have purposes on educational practices. Therefore, it assigns to evaluation important meanings that contemplate from a selective view to a diagnostic and emancipatory vision, and, in this last perspective,the evaluation practices can serve as instruments that potentiate transformations, based on decisions taken, aiming at a qualification of student learning, the research as a pedagogical initiative and the autonomy of those involved in educational actions. The study reverberated the understanding of evaluation as a process, having the concearn of part of the teachers with an evaluation trajectory consistent with the pedagogical practice and also that provide students moments in which they can learn significantly. It points out the urgency of investments in continuing teacher education and in the appreciation of the profession, as well as indicating the relevance of the democratization of education as the right of all.
A presente dissertação objetivou investigar a concepção e o processo de avaliação na área de Matemática presentes nos documentos oficiais e nas práticas avaliativas vinculadas ao Ensino Médio Politécnico no Rio Grande do Sul, exclusivamente em uma escola estadual no município de Caxias do Sul, região de abrangência da 4ª CRE, no período de 2012 a 2016. O aporte teórico que referenda o presente estudo ancora-se em Freire (1986, 1996, 2001), Afonso (2000), Garcia (2000), Vasconcellos (1998), Esteban (2000), Hoffmann (1993), Luckesi (2018), Saul (1994, 2000, 2015), entre outros. Trata-se de uma investigação de abordagem qualitativa e o método utilizado é o Estudo de Caso. A formação do corpus da pesquisa iniciou com a leitura e compilação de documentos institucionais, como o Regimento Escolar e o Projeto Político Pedagógico. Entrevistas com professores de Matemática e alguns membros da gestão escolar que participaram da implementação do Ensino Médio Politécnico na referida escola somaram-se à composição da construção dos dados. Para análise e tratamento de dados, contou-se com a Análise Textual Discursiva de Moraes; Galiazzi (2011), sendo possível a formação de quatro categorias que contemplam avanços significativos a partir de uma perspectiva de avaliação emancipatória, do envolvimento dos sujeitos comprometidos com a transformação da escola, das resistências e de caminhos formativos alternativos para uma formação docente qualificada e contínua. Os resultados apontam a importância da reflexão acerca das percepções e a qualificação dos envolvidos nos processos educativos, pois as ações pedagógicas possuem intencionalidades nas práticas educativas. Portanto, atribui à avaliação significados importantes que contemplam desde uma visão seletiva a uma visão diagnóstica e emancipatória. E nesta última perspectiva, as práticas avaliativas podem servir como instrumentos potencializadores de transformações, a partir de decisões tomadas, objetivando a qualificação do aprendizado discente, a pesquisa como princípio pedagógico e a autonomia dos envolvidos nas ações educativas. O estudo reverberou o entendimento da avaliação como processo, havendo a preocupação de parte dos docentes com uma trajetória avaliativa coerente com a prática pedagógica e que propicie aos estudantes momentos em que possam aprender significativamente. Ainda, aponta urgência de investimentos na formação continuada de professores e na valorização da profissão, bem como sinaliza a relevância da democratização da educação como direito de todos.
Keywords: Ensino médio - Caxias do Sul (RS); Ensino técnico - Caxias do Sul (RS); Matemática - Estudo e ensino; Avaliação; High school - Caxias do Sul (Brazil); Technical education - Caxias do Sul (Brazil); Mathematics - Study and Teaching; Evaluation